Simulation of atomic level width controlled graphene Nanoribbon field effect transistors and an ab initio study of h 2 o molecules adsorption on semiconducting GNR - Ali, Abrar Mohammad; Gharami, Devleena; Mimi, Niger Sultana (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.